Utopias Tried and Tested: Pueblos-Hospitales de Santa Fe and Cofradías in Early Colonial Mexico - Dierksmeier, Laura (Confraternitas, 2022)
This article compares sixteenth-century Mexican confraternities (est. since 1527) with the utopian hospital-towns of Vasco de Quiroga, est. in 1530 and 1533–4. Although likewise oriented towards the Christian moral ideals of charity and solidarity, and driven by kindred utopian aspirations and missionizing zeal, the institutions displayed notable differences in their daily operations and governing structures. These differences, the article shows, can be explained by a diverging understanding of the ideal of equality. Whereas Mexican confraternities embraced extant ethnic and individual diversity, aspiring only to as much equality as necessary for the execution of their charitable mission, the vision behind Quiroga’s hospitales espoused civilizational homogeneity, aiming to accomplish as much equality as possible. Consequently, confraternal institutions were run largely “bottom-up” and in a much more open and inclusive manner than the paternalistic “top-down” style of administration characteristic of Quiroga’s hospitales.